Manifestations of health associated with environmental elements: the case of the occurrence of coccidioidemycosis in Mexico 2004-2015 - Manzanares, Jose Luis (Población y Salud en Mesoamérica, 2017)
Objective: To analyze the temporal dynamics of coccidioide mycosis in Mexico, during the period between 2004-2015 in the context of its socio-environmental determinants and to identify its actual distribution in the national territory by means of the construction of geographical concentration indicators. Methods: An exploratory analysis of data was made from micro data on hospital discharges in the period 2004-2015. In theoretical terms, this research is located in the paradigm on social and environmental determinants of public health conditions. Results: The time evolution during 11 years of analyzed information allows to identify a persistent pattern in the concentration of cases, which mainly affects four states in the country, with a clear burden for the male population. The state of Sonora was identified as the entity with the highest incidence in Mexico, an entity that determines the environmental factors analyzed and the need to implement preventive public policies. Conclusions: Given the temporal evolution of hospital discharges due to coccidioid mycosis in Mexico and the environmental link of the disease, the evidence obtained represents an opportunity to intervene through control strategies focused on specific territories, with the State of Sonora being a priority site of attention.